Harmonization of technology across an integrated delivery network. (15th July 2018) - Anderson, Jared; Cooley, Thomas; De la Torre, Charlie; Della Rocco, James Anthony; Dorn, Mitchell; Ferer, Darren S.; Friudenberg, Patrick; Ganio, Michael; Lim, Dennison; McGregory, Michael; Nickman, Nancy A.; Schenkat, Daniel; et al.
Abstract : Purpose: A standardized blueprint for use when harmonizing or standardizing pharmacy automation and technology resources across individual institutions or an integrated delivery network (IDN) of institutions is described. Summary: Whether to strive for standardization (use of the same vendors and equipment) versus harmonization (use of various technologies to meet patient-specific needs and organizational stability requirements) and how to coordinate activities across IDNs consisting of 3–30 or more hospitals are common questions due to consolidations in the healthcare industry. For most IDNs with legacy systems, harmonization may be the better option. Large-scale harmonization initiatives require significant planning and coordination involving all affected parties. Detailed project plans should include the compiling of all associated harmonization costs that involve human resources, information on ongoing services and equipment, and program schedules for multiple concurrent projects in order to provide a framework for planning and coordination. Part of the planning process for harmonization efforts should include an extensive current-state analysis that includes review of contracts and vendors. Final harmonization decisions should be based on a mix of vendor recommendations, best practices, and accommodation of current practices that result in the lowest complexity of system redesign with regard to existing systems. When harmonizing existing technologies, planning must also consider the impact of the change to both the organization and individual users. Conclusion: Harmonization is an evaluative process whereby process variation due to automation and technology variability can be reduced and organizational interoperability to meet patient-specific needs can be promoted.